Perkara Perbuatan Melawan Hukum dalam Sengketa Ekonomi Syariah - Muhammad Nurcholis Alhadi (Jurnal Program Pascasarjana Ilmu Hukum Universitas Islam As-Syafi'iyah, 2021)
ABSTRACT This observe pursuits to evaluate conceptual heritage from the authority of The Religious Court for case of tort in dispute of Islamic financial system and attention of the decide in figuring out from the authority for case of tort in dispute of Islamic financial system. This observe makes use of a version of normative studies. The observe changed into performed via way of means of analyzing the library substances or secondary data. Data had been analyzed the usage of qualitative methods. The evaluation changed into performed via way of means of classifying, evaluating and linking to similarly systematically organized in accordance grooves its discussion. Based at the studies performed changed into concluded as follows: (1) The Religious Court authority, especially on sharia financial system in Law No. three of 2006 on First Amendment to Law No. 7 of 1989 at the Judiciary Religion is a shape of the government's solution to satisfy the want for the presence of the judiciary that handles disputes bobbing up from monetary pastime primarily based totally on sharia Islamic regulation. This association is a shape of responsive prison product as it displays a experience of justice and meet the expectancies of society. Tort case in Islamic economics has now no longer been set in KHES in order that preparations withinside the Civil Code may be used as supply fabric for substantial regulation remains according with the idea of Al Fi'lu Al Dhar and Al Maqasid As Sharia; (2) Consideration of the decide in figuring out from the authority for case of tort in dispute of Islamic financial system is that the man or woman and/or prison entities which can be events to the dispute have entered right into a prison dating this is primarily based totally on Islamic concepts and tort has a near connection or due to the prison dating.